KAJIAN PENGEMBANGAN SISI UDARA BANDAR UDARA JAPURA KABUPATEN INDRAGIRI HULU - Hazanawati, Hazanawati; Sartono, Wardhani (Civil Engineering Forum Teknik Sipil, 2008)
Today Japura airport is needed for actives again to give a more optimum service now and in the future especially for the great increase of passengers and the airplane traffic also other supporting factor. Analysis for measure the length of the runway, apron capacity and taxiway dimension that matches the needs based on the planning airplanes, which are Fokker and B 737-400, it is expected to give the airport operational performance as an effort to anticipate the development in the future. This study use on runway, apron and taxiway is conducted to measure the length of the runway, apron capacity and taxiway dimension that matches the needs based on the planning airplane, which are Fokker and B 737-400. This paper uses ICAO (International Cooperation Aviation Organization) and FAA (Federal Aviation Association) methods and JICA (Japan International Corporation Agency) formula (1991) for calculation of apron peak hour capacity. The analysis result shows that the length of runway that is needed for airplane type Fokker-50 is 1. 253 m and B 737-400 is 2.100 m, while the existing length of runway is 1.300 m. The width of runway according to ICAO and FAA standard is 30 m, the same with the existed landing field (runway). While the width of the taxiway according to ICAO and FAA standard by using planned airplane type Fokker-50 is 16, 62 m and B 737-400 is 15 m, narrower than the existed taxiway that is 23, 0 m. The existed apron dimension airplane is 80 m in length and 60 m in width, dimension apron using the planning airplane type Fokker-50 is 80 m x 52 m and B 737-400 is 173 m x 123 m. for the next 20 years, the pavements layers width, at runway, taxiway and apron, it doesn’t need to increase